2008
DOI: 10.1002/pros.20836
|View full text |Cite
|
Sign up to set email alerts
|

Unmethylated E‐Cadherin gene expression is significantly associated with metastatic human prostate cancer cells in bone

Abstract: The study clearly demonstrated a significant association of the concurrent expression of unmethylated E-cadherin gene and E-cadherin protein with metastatic prostate cancer cells in bone, and that its expression may have a role in the intercellular adhesion in the formation of metastatic lesions in bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…On the other hand some recent articles objected to this issue. Saha et al (27) reported that loss of e-cadherin gene expression is caused by reversible epigenetic mechanisms, and showed that e-cadherin gene expression was present in metastatic bone lesions of prostate carcinoma. it was hypothesized that e-cadherin gene expression might be the last fact to provide advantage tumor cells to make clusters in metastatic areas (26).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand some recent articles objected to this issue. Saha et al (27) reported that loss of e-cadherin gene expression is caused by reversible epigenetic mechanisms, and showed that e-cadherin gene expression was present in metastatic bone lesions of prostate carcinoma. it was hypothesized that e-cadherin gene expression might be the last fact to provide advantage tumor cells to make clusters in metastatic areas (26).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, enhancer of zeste homolog 2 (EZH2), which is involved in gene silencing by histone methylation, is overexpressed in advanced PC and can mediate the silencing of E-cadherin [166]. Interestingly, a survey of primary PC samples and metastatic bone biopsies showed that 70 % of primary PC samples have a methylated E-cadherin promoter with heterogeneous E-cadherin expression, while 87 % of metastatic bone biopsies contain an unmethylated E-cadherin promoter with homogenous E-cadherin expression [167]. Together, these results demonstrate that EMT can be epigenetically regulated and provide a mechanism linking EMT with PC progression.…”
Section: Preclinical Evidence Of Ep In Pcmentioning
confidence: 99%
“…Chromatin immunoprecipitation (CHIP) analysis showed that MMSET binds directly to TWIST1 locus, suggesting a direct role of MMSET in the regulation of TWIST1 expression [84]. The classical epithelial marker E-cadherin is often found to be silenced in PCa due to promoter methylation [8586]. It is intriguing to note that methylation of E-cadherin is a priming event that helps in creating a permissive environment for outgrowth and continued morphogenesis of prostatic ducts at different stages of the development [87].…”
Section: Extracellular Signals To Regulate Emtmentioning
confidence: 99%